Analyzing higher order thinking skills (HOTS) questions of reading essay tasks in senior high school English textbook - Maziyyatus Shalihah; Mutmainnah Mustofa; Dzulfikri Dzulfikri (English Education Journal, 2022)
English textbooks, particularly for senior high school students, should provide competent English reading activities to help students improve their English skills by simultaneously training them in reading and vocabulary knowledge. The researcher aims to investigate the Higher Order Thinking Skills (HOTS) in essay reading exercises distributed in the English SMK/MAK textbook for grades X, XI, and XII. The researcher selected the English textbook published by Bumi Aksara. This study was carried out using the qualitative method.. The data analysis method was sequentially started from textbook observation, question selection, data reduction, and finally the HOTS data analysis. According to the results, there are 6 HOTS reading essay questions (C4: 2, C5: 4) in the English textbook for X grade, 7 HOTS reading essay questions (C4: 5, C5: 2) in the English textbook for XI grade, and 12 HOTS reading essay questions (C5: 12) in the English textbook for XII grade. It can be concluded from the findings that HOTS reading essay questions are distributed less than LOTS. These results may suggest to English teachers to be selective in utilizing English textbooks to improve student's critical thinking and for the further researcher to investigate HOTS effects on students’ achievement.